2021
DOI: 10.1038/s41598-021-88947-5
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear radiative Maxwell nanofluid flow in a Darcy–Forchheimer permeable media over a stretching cylinder with chemical reaction and bioconvection

Abstract: Studies accentuating nanomaterials suspensions and flow traits in the view of their applications are the focus of the present study. Especially, the usage of such materials in biomedical rheological models has achieved great importance. The nanofluids’ role is essential in the cooling of small electronic gizmos like microchips and akin devices. Having such exciting and practical applications of nanofluids our goal is to scrutinize the Maxwell MHD nanofluid flow over an extended cylinder with nonlinear thermal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 63 publications
0
15
0
Order By: Relevance
“…By involving energy and reaction over a parabolic surface using a finite element approach, Y. M. Chu et al [15] examine the enhancement of thermal energy and solute particles using hybrid nanoparticles. References [16,17] provide additional details.…”
Section: Introductionmentioning
confidence: 99%
“…By involving energy and reaction over a parabolic surface using a finite element approach, Y. M. Chu et al [15] examine the enhancement of thermal energy and solute particles using hybrid nanoparticles. References [16,17] provide additional details.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of chemical reaction, heat radiation, and the incoming porosity factor due to porous media on free stream convection and magnetized Carreau fluid flow toward a stretching cylindrical surface were examined in Lim et al [11]. Liu et al [12] looked at a stretching cylindrical surface with chemical reaction as well as the bio-convection and a radiative (nonlinear term appearing in it) Maxwell type nanofluid flow in a Darcy-Forchheimer (porous) medium. Alarabi et al [13] demonstrated the hybrid nanofluid convection for Darcy medium with the involvement of heterogeneous-homogeneous chemical processes and magnetic impact characteristics past an extending or contracting cylindrical surface with the impact of Joule heating using Al 2 O 3 + Cu nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Zhou et al 25 used the constant effect of suction/injection to optimize the von Karman revolving flow for Maxwell fluid passing over a penetrating disc. Liu et al 26 scrutinized the MHD flow of Maxwell nanofluid over a stretched cylinder. Electrically conducting hybrid nanofluid was utilized by Aziz et al 27 to study entropy, heat transfer as well as flow on horizontal porous shrinking sheet.…”
Section: Introductionmentioning
confidence: 99%